Pedagogy of sport as a subdiscipline of educational science - Arkadiusz Kaźmierczak (Kazimierz Wielki University, 2018)
The scientific dimension of sport along with its educational values contributed to the creation of a new subdiscipline in the pedagogical sciences referred to as sports pedagogy. The baron Pierre de Coubertin can be regarded as an ancestor of this term, who almost to the last years of his life, with great enthusiasm and commitment, presented his views on sporting education in the press, in compact positions and public lectures, constantly emphasizing the importance of sporting activity in the process of education and shaping the personality of the young generation. Currently, many theoreticians define sport pedagogy as a scientific subdiscipline related to sport (along with related fields of science), which should be considered in three dimensions in the subject of research; knowledge in the historical, political and social context, relations (cooperation) of foster children in the field of sport activity and its pedagogical consequences; and social interaction in a coach / teacher - foster-child relationship